Polynomial Primal-Dual Cone Affine Scaling for Semidefinite Programming - Arjan B. Berkelaar; Jos F. Sturm; Shuzhong Zhang (Tinbergen Institute, 1997)
In this paper we generalize the primal–dual cone affine scaling algorithm of Sturm and Zhang to semidefinite programming.We show in this paper that the underlying ideas of the cone affine scaling algorithm can be naturely applied to semidefiniteprogramming, resulting in a new algorithm. Compared to other primal–dual affine scaling algorithms for semidefiniteprogramming (see, De Klerk, Roos and Terlaky), our algorithm enjoys the lowest computationalcomplexity.
Keywords: 330; Semidefinite Programming; Affine Scaling; Primal-Dual Interior Point Methods; Mathematische Optimierung; Theorie